ANALISIS WEBSITE QUALITY, TRUST DAN LOYALTY PELANGGAN ONLINE SHOP - Hotlan Siagian; Edwin Cahyono (Institute of Research and Community Outreach - Petra Christian University, 2014)
The use of online store as purchasing media of goods and services increased rapidly in Indonesia. The number of online store owners also rose sharply such that competition unavoidable. Website quality is one of the factors that influece trust and trust will generate loyalty of the online shop customer. This research aimed to analyze the influence of website quality on trust and the influence trust on customer loyalty in East Java area. The research was conducted by distributing questionnaires to 249 respondens which selected randamly at Petra Christian University campuss. Data was analyzed using SPSS for Windows Version 16 and SmartPLS Version 1.01. The results obtained, website quality influence trust, and trust influence customer loyalty.